Extraocular Muscles Tension, Tonus, and Proprioception in Infantile Strabismus: Role of the Oculomotor System in the Pathogenesis of Infantile Strabismus—Review of the Literature - Costantino Schiavi (Scientifica)
The role played by the extraocular muscles (EOMs) in the etiology of concomitant infantile strabismus is still debated and it has not yet definitively established if the sensory anomalies in concomitant strabismus are a consequence or a primary cause of the deviation. The commonest theory supposes that most strabismus results from abnormal innervation of the EOMs, but the cause of this dysfunction and its origin, whether central or peripheral, are still unknown. The interaction between sensory factors and innervational factors, that is, esotonus, accommodation, convergence, divergence, and vestibular reflexes in visually immature infants with family predisposition, is suspected to create conditions that prevent binocular alignment from stabilizing and strengthening. Some role in the onset of fixation instability and infantile strabismus could be played by the feedback control of eye movements and by dysfunction of eye muscle proprioception during the critical period of development of the visual sensory system. A possible role in the onset, maintenance, or worsening of the deviation of abnormalities of muscle force which have their clinical equivalent in eye muscle overaction and underaction has been investigated under either isometric or isotonic conditions, and in essence no significant anomalies of muscle force have been found in concomitant strabismus.